Hydrogeology of Mangsri Cave, Gunungsewu Karst Area, Java Island, Indonesia - Cahyadi, Ahmad; Reinhart, Hilary; Wahyu Ristiawan, Angga; Dwi Putra, Rakhmat; Labib, M. Ainul; Naufal, Muhammad; Agus Riyanto, Indra; Ramadhan, Fajri; Dwi Laksono, Angga (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
The Gunungsewu karst area is not only known for its unique landscape but also its recurring drought events. To meet the water supply, the local population utilizes several water potentials, namely doline pond, spring, and underground river. This study was designed to analyze the hydrogeological conditions of Mbangsri Cave, following its accidental discovery by the community at the end of 2018. The hydrogeological analysis was conducted by geological surveys, which consisted of rocks collection and structural measurements, cave mapping, and recharge area delineation based on remote sensing images acquired by unmanned aerial vehicles. The results showed that Mbangsri Cave, in the hydrogeological perspective, had low water resources potential. It is believed to be the result of (1) relatively small catchment area, (2) a fault in the southern part of Mbangsri Cave, creating a small groundwater basin, and (3) the thin epikarst layer, limiting the water storage.